Marketing Strategy in Increasing the Number of Sales of Goods Using Soar Analysis in Grocery Stores in Pondok Cabe, South Tangerang - Septiani, Fauziah; Hidayat, Nandang; Hardhienata, Soewarto (International Journal of Business and Applied Economics, 2025)
This study aims to analyze effective marketing strategies for increasing sales of goods in grocery stores located in Pondok Cabe, South Tangerang, using the SOAR (Strengths, Opportunities, Aspirations, Results) analysis method. Through a qualitative approaches, data were collected from surveys and interviews with store owners and customers. Strengths: The research identifies the strengths of grocery stores, such as strategic location, product variety, and good cust omer service.Opportunities: The analysis explores existing opportunities, including the trend of online shopping and increasing consumer awareness of local products. Aspirations: The study investigates the aspirations of store owners to enhance sales, such as brand development and improving the shopping experience. Results: Findings indicate that implementing marketing strategies based on SOAR analysis can significantly boost sales, with recommendations to leverage social media and local promotions. This research is expected to provide insights for grocery store owners in formulating more effective and sustainable marketing strategies.